Dasar Pertimbangan Jaksa Kejaksaan Tinggi Sumatera Barat Dalam Menangani Perkara Obligasi Negara Yang Kedaluwarsa (Studi Kasus Perkara Nomor 158/PDT.G/2021/PN.PDG) - Aulia Falillah; Elwidarifa Marwenny (GLOBAL SCIENTS PUBLISHER, 2025)
Bonds are debt certificates issued by an agency or company that make the party issuing the bond indebted to the buyer and owner of the bond. One of the bond cases handled by the West Sumatra High Prosecutor's Office is case Nomor 158/PDT.G/2021/PN.PDG. This case began when the Plaintiff, who was the heir of one of the owners of the State Bond, sued the government with an expired state bond case. Then the judge decided to grant the Plaintiff's claim. The decision contradicts KMK Nomor 466a/KMK.011/1978 which states that the language of the bond claim is Nomor longer valid after 5 years have passed, while the lawsuit was filed 72 years ago. The judge's decision also contradicts the Prosecutor's Exception. The formulation of the problem in writing includes: 1) What is the basis for the Prosecutor's considerations in defending the state in the expired bond case Nomor 158/PDT.G/PN.PDG; 2) What are the obstacles faced by the Prosecutor as a State Attorney in handling the expired bond case case Nomor 158/PDT.G/PN.PDG. To answer this question, an Empirical Juridical research type was used with an interview technique using a semi-structured interview model. The type of approach used in the study was a case study and the following conclusions were drawn: 1) In this case, the Prosecutor stated that there was an error in the authority to try, the plaintiff's legal standing was unclear, the claim had expired based on KMK 466a/1978, the explanation of the legal basis and procedures for issuing bonds was incomplete and there was Nomor adequate explanation of the alleged unlawful act.; 2) The main obstacle faced by the Prosecutor in handling this bond case was the limited evidence. Suggestions for the obstacles faced by the Prosecutor include the need to create an integrated digital archiving system to store important state documents. Create a special database for state bond documentation. Preserve and digitize ancient documents to prevent further damage and improve the Prosecutor's competence in handling bond cases.